2010
DOI: 10.1111/j.1444-0938.2010.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact lenses as a drug delivery device for epidermal growth factor in the treatment of ocular wounds

Abstract: Background: This work was conducted to investigate the uptake and release of epidermal growth factor (EGF) from hydrogel contact lenses and to determine whether the released protein would be therapeutically active in a rabbit corneal epithelial defect model of ocular trauma, prior to use in humans. Methods:The uptake and release of EGF from hydrogel contact lens materials were determined by high-pressure liquid chromatography. Contact lenses composed of vasurfilcon A or lotrafilcon A (containing silicone) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…38 Interestingly, though EGF alone induced rapid reepithelialization, the regenerating cells were loosely bound to the corneal BM, indicating the necessity for coapplication of adhesion-like molecules to facilitate stability. 39 Our system has this added potential because VN is known to couple growth factors such as insulin-like growth factor-binding proteins (IGF-BPs), which partake in corneal 48 and cutaneous 49 wound repair. VN/IGF-BP complexes are also supportive factors for cultured SCs, 50 and VN, FN, and nerve growth factor have each been found to promote the healing of persistent corneal epithelial defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Interestingly, though EGF alone induced rapid reepithelialization, the regenerating cells were loosely bound to the corneal BM, indicating the necessity for coapplication of adhesion-like molecules to facilitate stability. 39 Our system has this added potential because VN is known to couple growth factors such as insulin-like growth factor-binding proteins (IGF-BPs), which partake in corneal 48 and cutaneous 49 wound repair. VN/IGF-BP complexes are also supportive factors for cultured SCs, 50 and VN, FN, and nerve growth factor have each been found to promote the healing of persistent corneal epithelial defects.…”
Section: Discussionmentioning
confidence: 99%
“…Application of recombinant proteins could be a standardized approach for treating ocular surface disorders that do not require a cell-based therapy, including persistent epithelial defects. 37,44 -47 Indeed, CLs have been used to deliver EGF to wounded corneas, 39 and pharmacologic agents have been absorbed onto lenses for glaucoma management. 38 Interestingly, though EGF alone induced rapid reepithelialization, the regenerating cells were loosely bound to the corneal BM, indicating the necessity for coapplication of adhesion-like molecules to facilitate stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study design was partially based on previous work by Schultz et al, who showed that EGF, HGH, and dexamethasone delivered through a contact lens delivery system, could accelerate wound healing in a New Zealand white rabbit corneal debridement model. 94,95 They showed that the molecular structure of EGF and rHGH were not altered upon release from the contact lens hydrogel in the New Zealand white rabbit corneal debridement model. Such a local delivery scheme using a polymer vehicle allows a safe and sustainable release system translatable to clinical applications and is ideal for delivery of a protein.…”
Section: Treatment Of Persistent Corneal Epithelial Defectsmentioning
confidence: 99%
“…Over 90% of surveyed contact lens fitters expressed an interest in the development of drug-releasing contact lens materials. 5 The uptake and subsequent release of pharmaceutical agents have been the topic of much recent research, and published work has demonstrated the release of many topical drugs from commercial soft lens materials, including fluoroquinolones, 6-8 cromolyn sodium, 9 ketotifen, 9,10 ketorolac, 9 dexamethasone, 9,11 epidermal growth factor, 12 and timolol. 13 Although the release of topical therapeutic drugs from soft lenses may be advantageous for treating ocular surface disease, the uptake and subsequent release of components from disinfection systems have proven to be a negative factor.…”
mentioning
confidence: 99%